Pengaruh Waktu Ekstraksi Daun Jeruk Nipis (Citrus aurantifolia) Menggunakan Pelarut n-Heksana terhadap Rendemen Minyak - Nasrun Ibrahim; Jalaluddin Jalaluddin; Nurul Rahmah (Jurnal Teknologi Kimia Unimal, 2019)
Indonesia has natural resources that are rich in essential oils. One potential natural resource is lime which can be used as flavor in food. The extraction of lime leaf essential oil using volatile solvent extraction method. The aim of the study was to determine the effect of extraction time on yield, refractive index, and density of essential oils produced. Extraction of lime leaf oil with n-hexane solvent using soxhlet extractors. The old lime leaves that have been cleaned, cut into small pieces and wrapped in filter paper and put in soxhlet. 200 ml n-hexane solvent is inserted in an extractor round bottom flask equipped with coolant. Extraction is carried out at a certain temperature and time depending on the type of solvent used, until the solvent color is returned as before. Then the filtrate was distilled to be purified, so that lime leaf oil was obtained separately from the solvent. Essential oils are then tested for yield, refractive index, and density contained in essential oils. The results of the study were extraction of lime leaves with n-hexane solvent, the highest yield obtained at a sample weightof 200 grams with an extraction time of 180 minutes which was 3.11%. The highest oil refractive index was also obtained at a sample weight of 200 grams with an extraction time of 180 minutes which was 1.47, while the density of essential oil from lime leaves was 0.79gr/ml.Keywords: essential oil, lime leaf, extraction, n-heksana